Financial Feasibility Agroindustri Households Based On Tambers "Case Study In The Industrial Household Tambers at Kelurahan Naimata, Kecamatant Maulafa, Kota Kupang") - Modesta R Menggol; Wiendiyati Wiendiyati; Sondang S. P. Pudjiastuti (Buletin Ilmiah Impas, 2022)
Beef is a red meat derived from cattle that can be in a few practical foods that are much liked by the community such as, shredded beef and beef jerky. One of the household industry that is engaged in the processing of beef into a practical food is the household industry "Tambers". A feasibility study is required to see an overview of whether or not an attempt is exercised. The research aims to analyse the financial feasibility of Tambers ' agro-industry. The study was conducted from November 2019 to December 2019. The data collection methods used are survey locations and direct interviews with respondents, while also using literature and documentation methods. Data analysis is conducted using financial feasibility analysis; NET Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), Payback Period (PBP), Break Event Point (BEP), and after financing analysis. Results of financial feasibility analysis IRT Tambers year 2015-2019 stated worthy of Net Present Value value of Rp. 361,339,588,-that is positive (NPV > 0), Internal Rate of Return (IRR) 56.73% where the IRR is greater than the prevailing interest rate of 12%, and Net B/C is 2.47 where Net B/C > 1. The results of an after financing analysis with a 9% interest rate which is the interest rate given for SMES to declare that assuming the loan capital up to 100%, IRT Tambers are still in the criteria worthy to be executed evidenced by the eligibility criteria that gave positive results.